AB0758 Subclinical Atherosclerosis is not Accelerated in Well-Controlled Ankylosing Spondylitis: Original Data and Meta-Analysis of Published Studies. (9th June 2015) - Arida, A.; Protogerou, A.D.; Konstantonis, G.; Konsta, M.; Delicha, E.; Kitas, G.D.; Sfikakis, P.P.
Abstract : Background: Chronic inflammatory rheumatic diseases associate with increased risk of cardiovascular disease (CVD) in part due to accelerated atherosclerosis. While this is well established for rheumatoid arthritis (1), data on ankylosing spondylitis (AS) is limited and the relative contribution of inflammation versus classical cardiovascular risk factors remains a matter of controversy (2). Objectives: To address this controversy in an original, carefully designed study of subclinical atherosclerosis in AS patients, as well as in a meta-analysis of previous studies. Methods: Atheromatic plaques in carotid and femoral arteries, carotid hypertrophy (intima-media thickness-IMT; cross sectional area) and carotid stiffness by ultrasound, as well as aortic stiffness by pulse wave velocity were examined in consecutive non-diabetic CVD-free, AS patients. Apparently healthy individuals carefully matched 1:1 with patients for age, gender, smoking, dyslipidemia and hypertension served as controls. A meta-analysis of those studies that examined subclinical atherosclerosis in AS patients versus controls with comparable CVD risk factors, published up to June 2014, was also performed. Studies were subsequently stratified according to the mean level of disease activity (BASDAI> or <4), and the proportion of patients receiving anti-TNF biological therapy (> or <50%). Results: In this contemporary cohort comprising of 67 AS patients (82% men), aged 47.5+12.5 years (mean ± SD), with median disease duration of 12 years and BASDAI of 1.8 (IQR 0.4-3.6), of whom 66% were receiving anti-TNF treatment, atheromatic plaques were slightly less prevalent compared to controls. Moreover, carotid hypertrophy and stiffness, as well as aortic stiffness, were comparable between patients and their matched controls. Meta-analysis and meta-regression analysis of 14 studies, including the present study, revealed that carotid IMT is significantly increased in AS patients versus controls. On the other hand, analysis of those studies examining also the presence of carotid plaques revealed no statistical difference in the relative risk of the presence of carotid plaques between AS patients and their matched controls. Interestingly, however, increased IMT was not evident in studies involving well-controlled patients (mean BASDAI <4) or in those studies which included >50% of anti-TNF-treated patients. Conclusions: Subclinical atherosclerosis is not accelerated in well-controlled AS patients. References: Peters MJ, et al. EULAR evidence-based recommendations for cardiovascular risk management in patients with rheumatoid arthritis and other forms of inflammatory arthritis. Ann Rheum Dis 2010;69:325-31. Mathieu S, et al. Cardiovascular profile in ankylosing spondylitis: a systematic review and meta-analysis. Arthritis Care Res 2011;4:557-63. Disclosure of Interest: None declared